2020
DOI: 10.1109/access.2020.3006512
|View full text |Cite
|
Sign up to set email alerts
|

Single Low-Dose CT Image Denoising Using a Generative Adversarial Network With Modified U-Net Generator and Multi-Level Discriminator

Abstract: Low-dose CT (LDCT) images have been widely applied in the medical imaging field due to the potential risk of exposing patients to X-ray radiations. Given the fact that reducing the radiation dose may result in increased noise and artifacts, methods that can eliminate the noise and artifacts in the LDCT image have drawn increasing attentions and produced impressive results over the past decades. However, recent proposed methods mostly suffer from noise remaining, over-smoothing structures or false lesions deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…Besides, the data-driven learning method can adapt to any noise type effectively [ 83 ]. Hence, it improves the overall performance of LDCT restoration and possesses a novel advantage over other LDCT restoration methods [ 6 , 46 ].…”
Section: Overview Of Ldct Restorationmentioning
confidence: 99%
See 4 more Smart Citations
“…Besides, the data-driven learning method can adapt to any noise type effectively [ 83 ]. Hence, it improves the overall performance of LDCT restoration and possesses a novel advantage over other LDCT restoration methods [ 6 , 46 ].…”
Section: Overview Of Ldct Restorationmentioning
confidence: 99%
“…Different from residual connections, the concatenation type skip connections in U-net allow transferring of more feature information forward, and it is a significant performance aspect in U-net architecture [ 44 ]. Furthermore, it has been observed that almost all of the U-net-based LDCT restoration applications reviewed in this study have been published by integrating U-net with the Generative Adversarial Network (GAN) s [ 6 , 45 ]. However, after publishing the Pix-to-Pix GAN by Isola et al [ 31 ], there were several LDCT restoration applications published based on it.…”
Section: Architecturesmentioning
confidence: 99%
See 3 more Smart Citations